2016
DOI: 10.2459/jcm.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

T2238C ANP gene variant and risk of recurrent acute coronary syndromes in an Italian cohort of ischemic heart disease patients

Abstract: The present results demonstrate that C2238/ANP-minor allele carrier status is an independent risk factor for ACS recurrence in an Italian cohort of ischemic heart disease patients over the long term, and they support the role of C2238/ANP-minor allele as a negative prognostic factor in coronary artery disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…A previous study performed by a research group from our university showed that the A2A2 allele is associated with a higher incidence of histories of non-fatal myocardial infarction and more extensive CAD [ 20 ]. More recently Rubattu et al demonstrated that ANP polymorphism is associated with higher risk for an acute coronary syndrome recurrence in patients with CAD [ 21 ]. Moreover, a recently published meta-analysis indicated that ANP 2238 T/C polymorphism is related to increased risk of ischaemic stroke [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study performed by a research group from our university showed that the A2A2 allele is associated with a higher incidence of histories of non-fatal myocardial infarction and more extensive CAD [ 20 ]. More recently Rubattu et al demonstrated that ANP polymorphism is associated with higher risk for an acute coronary syndrome recurrence in patients with CAD [ 21 ]. Moreover, a recently published meta-analysis indicated that ANP 2238 T/C polymorphism is related to increased risk of ischaemic stroke [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the markers that are associated with reACS have also been identified in recent years. Rubattu et al showed that the 2238C ANP gene variant is associated with recurrent ACS (7). Kume N et al determined that lectin-like oxidized low density lipoprotein receptor-1 (LOX -1) in circulation predicted recurrent ACS and mortality (8).…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical and laboratory parameters associated with mortality in patients with CAD were studied (5,6). However, affordable and easily accessible biomarker-based studies that are related to re-ACS are still scarce (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Several case-control association studies were performed in the attempt to explore the pathological relevance of the T2238C transition. As a result, an association of the C2238 allele with an increased risk of both myocardial infarction and stroke was reported in different cohorts, including Caucasian and Asian populations [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Moreover, carriers of this variant allele showed an increased risk of recurrent ischemic stroke and of myocardial infarction [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%